Infantile nephrotic syndrome - Nagi, N. A. (1974)
Four infants, two boys and two girls, with congenital nephrotic syndrome are reported in a single family. The disease process began during the first year of life. The disorder did not respond to corticosteroid therapy. One infant received cyclophosphamide therapy as well without avail. All four children died from intercurrent infection. The family tree is suggestive of an autosomal recessive inheritance.